Corporate Governance Country Assessment : Republic of Latvia - World Bank (Washington, DC, 2013)
This report provides an assessment of the corporate governance policy framework and enforcement and compliance practices in Latvia. Latvia has already invested considerable resources in upgrading its legislation to meet EU Directives, and the legislative and regulatory framework dealing with corporate governance issues is quite robust. Strengths and weaknesses are highlighted and policy recommendations made where appropriate. This report promotes private sector initiatives and capacity building to follow up on the legislative progress on corporate governance reform. It recommends the development of a Latvian or regional voluntary code of best practice of corporate governance.